Financing as a supply chain: The capital structure of banks and borrowers - Gornall, Will; Strebulaev, Ilya A. (Journal of Financial Economics, 2018)
We develop a model of the joint capital structure decisions of banks and their borrowers. Bank leverage of 85% or higher emerges because bank seniority both dramatically reduces bank asset volatility and incentivizes risk-taking by producing a skewed return distribution. Nonfinancial firms choose low leverage to protect their banks, presenting a partial resolution to the low-leverage puzzle. Our setup naturally extends to include government actions as we model bank assets using a modified Basel framework. Deposit insurance and bailout expectations lead banks and borrowers to take on more risk. Capital regulation lowers bank leverage but can increase bank risk due to a compensating increase in borrower leverage. Despite this, doubling current capital requirements reduces bank default risk by up to 90%, with only a small increase in loan interest rates.